2001
DOI: 10.1164/ajrccm.164.3.2009018
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Activity of the Diaphragm during Pressure Support Ventilation in Acute Respiratory Failure

Abstract: We compared crural diaphragm electrical activity (EAdi) with transdiaphragmatic pressure (Pdi) during varying levels of pressure support ventilation (PS) in 13 intubated patients. With changing PS, we found no evidence for changes in neuromechanical coupling of the diaphragm. From lowest to highest PS (2 cm H(2)O +/- 4 to 20 cm H(2)O +/- 7), tidal volume increased from 430 ml +/- 180 to 527 ml +/- 180 (p < 0.001). The inspiratory volume calculated during the period when EAdi increased to its peak did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 23 publications
4
125
2
5
Order By: Relevance
“…Neural inspiratory time (T in ) was defined, according to previously published NAVA studies [13][14][15]19], as the time difference between the initial increase and the maximal value of EAdi (EAdi max ). Details on this point are given in the Electronic Supplementary Material.…”
Section: Measurementsmentioning
confidence: 99%
“…Neural inspiratory time (T in ) was defined, according to previously published NAVA studies [13][14][15]19], as the time difference between the initial increase and the maximal value of EAdi (EAdi max ). Details on this point are given in the Electronic Supplementary Material.…”
Section: Measurementsmentioning
confidence: 99%
“…15 Moreover, the patient's neuro-ventilatory coupling needs to be intact in order for the intensity of the EA di signal (as an expression of the neuronal activity of the respiratory center) to be proportional to the patient's ventilatory requirement. This implies that all the receptors of the respiratory system's feedback mechanism are sufficiently functional and that their signals are interpreted correctly by the respiratory center.…”
Section: The Importance Of Patient-ventilator Synchronymentioning
confidence: 99%
“…Several publications have shown that there is usually a good correlation between the intensity of diaphragmatic electromyogram and transdiaphragmatic pressure. 15,16 Thus, the measure of E di could be useful to estimate the progression of a patient's inspiratory effort during recovery from Guillain-Barré syndrome. Nonetheless, further studies are needed to assess the safety of NAVA in patients with Guillain-Barré syndrome and to evaluate the best time to start the weaning process with this modality.…”
Section: Discussionmentioning
confidence: 99%